The role of zinc supplementation in humoral immune response to hepatitis B vaccination in infants: a double-blind randomized placebo-controlled trial - K. Suarca; Hendra S; B. N. P. Arhana; I K. G. Suandi (Paediatrica Indonesiana, 2008)
Background Suboptimal zinc intake may depress thymus function,lymphoproliferation, and T cell-dependent B-cell proliferation,which can impair antibody production. Zinc supplementation canimprove immune function and reduce morbidity.Objective To assess the effect of zinc supplementation on infants'anti-HBs titer after hepatitis B vaccination.Methods A double-blind randomized control trial of 66 healthyinfants in Pustu Dauh Puri, Denpasar Barat was conducted. Subjectswere followed from birth to three months of age and were placedinto two treatment groups using block randomization. One groupreceived zinc supplements with a standard hepatitis B vaccination(zinc group, n=33) and the other group received placebosupplements with standard hepatitis B vaccination (placebo group,n=33). The serum zinc levels were measured at baseline and atthree months. The difference in levels of anti-HBs titer between thezinc and placebo groups was the primary endpoint of this study.Results The serum zinc levels were significantly higher in the zincgroup compared to the placebo group (P = 0.017), with a meandifference of 18.76 miU/ml (95% CI 3.45 to 34.07). Regardlessof baseline serum zinc levels, the mean anti-HBs titers weresignificantly higher in the zinc group compared to the placebogroup (P <0.0001; mean difference = 495.8 miU/mL; 95%CI 362.32 to 629.44). Multivariate analysis showed that zincsupplementation was the only variable that influenced anti-HBstiter levels (P < 0.0001).Conclusion Regardless of their initial zinc serum level, infantsreceiving zinc supplements along with standard hepatitis Bvaccination have significantly higher levels of anti-HBs titersthan infants receiving hepatitis B vaccination without zincsupplements.